Kearifan Muhammadiyah di Sumatera Utara dalam Merespons Isu Radikalisme - Al Rasyidin; Hasnah Nasution (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2018)
Radicalism and terrorism have anxiously attracted the world community. Ironically, the terms have been labeled to Islam and the Muslims. This article focuses on how does Muhammadiyah as one of the Indonesian largest Islamic organizations respond to the issue of radicalism in Indonesia? Based on field research where the data is gathered through interview, observation, and documentary study, the research puts emphasis on the responses of Muhammadiyah toward the idea and movement which attempt to establish Islamic state; its responses to the Western countries and the unbelievers; its interpretation of jihad as an obligatory war against the unbelievers; and its idea on legalization of suicide bombings. The study indicates that Muhammadiyah, particularly in the North Sumatera, rejects any radical movement along with its ideology in Indonesia. Muhammadiyah sees that NKRI (The Unity State of the Republic of Indonesia) has been an ideal model of state and it is a blessing of God that must be preserved and protected. Muhammadiyah condemns anyone who justifies violent acts and commits murder and suicide bombings in the name of religion. Muhammadiyah also asserts that radicalism is a threat toward world peace and it has no correlation with the Islamic teachings.